2017
DOI: 10.1007/s11695-017-2885-1
|View full text |Cite
|
Sign up to set email alerts
|

Bile Gastritis Following Laparoscopic Single Anastomosis Gastric Bypass: Pilot Study to Assess Significance of Bilirubin Level in Gastric Aspirate

Abstract: The incidence of bile gastritis in this cohort is higher than reported in the literature, and this may be worrying. The correlation between endoscopic findings and patients' symptoms is poor. Bilirubin level and pH in aspirate might be useful tools to confirm alkaline reflux. Its level might help to choose candidates for revision surgery after SAGB. This needs further validation with larger sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The incidence of post-OAGB GERD has been reported from 0% to 30% in different studies. [ 5 9 10 11 13 14 15 18 30 31 32 33 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of post-OAGB GERD has been reported from 0% to 30% in different studies. [ 5 9 10 11 13 14 15 18 30 31 32 33 34 ]…”
Section: Resultsmentioning
confidence: 99%
“…MGB is a better alternative to Roux-en-Y gastric bypass (RYGB), as it has a shorter operative time, only one anastomosis, with rare incidence of internal herniation, shorter learning curve, easily reversed, with equivalent or even superior results in terms of weight loss [7][8][9][10]. Although biliary gastritis after MGB was discussed in many studies, yet the measuring of Bilirubin level in the pouch and its effect on the mucosa was mentioned only in the study done by shenouda et al, they reported that the rate of biliary gastritis after MGB reached 30%, and this is correlated with the level of bile in the pouch, Among 20 patients, the EBWL 6 months postoperatively was 74% (60-84), with no mortalities ,and one case of calf DVT 2 weeks after discharge [11]. In 2017, Carbajo reported in his study that follow up UGI endoscopy after 5 years revealed, mild to moderate pouch gastritis (8%), but there were no worrisome endoscopic or histological changes, mean operative time was 86 min (45-180).…”
Section: Discussionmentioning
confidence: 99%
“…The long, narrow gastric pouch and widely patent gastrojejunostomy proposed as likely mechanistic explanations [ 22 ]. Studies by Lasheen and Shenouda reported post-operative gastroesophagitis in 32.5% of patients at 9 months and 55% at 6 months, respectively; however, no comment was made about whether these findings were de novo post-operative findings or had been present pre-operatively [ 14 , 15 ]. Our study showed no association between de novo gastroesophagitis and positive reflux on scintigraphy, contrasting with a positive association reported by Saarinen’s group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%